Experimental and theoretical determination of the duration of surface runoff formation - Havryshchuk, V. V. (Харківський національний автомобільно-дорожній університет, 2021)
There are theoretical and experimental results of the study of the duration of surface runoff formation presented. The prospects of application of this method are defined at designing of sanitary technical measures on highways of public use and artificial constructions. There is prospective direction of increase of efficiency of sewerage rain network designing and local treatment facilities on highways defined. The issue of increasing the accuracy of hydraulic calculation has been studied. The main advantages of implementation of modern drainage solutions are investigated. It is proposed to use a monogram to determine the duration of the formation of surface concentration, in accordance with climatic characteristics.
Експериментальне та теоретичне визначення тривалості формування поверхневого стоку
Keywords: highway; slope; pavement; surface runoff; precipitation intensity; автомобільна дорога; похил; покриття; поверхневий стік; інтенсивність опадів; 621.863.2; 10.30977/BUL.2219-5548.2021.92.2.5